Analysis of Post-COVID-19 Guillain-Barré Syndrome over a Period of One Year in the University Hospital of Split (Croatia) - Niko Dunkić; Marija Nazlić; Valerija Dunkić; Ivica Bilić (MDPI AG, 2023)
The virus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) is capable of attacking the nervous system in several ways and leading to neurological diseases such as GBS (Guillain-Barré syndrome) through the resulting neurotropism and immune response. The aim of this study is to show the relationship between Coronavirus disease (COVID-19) and GBS and to better understand the clinical symptoms to prevent poor outcomes. Data from 15 patients were extracted from the Department of Neurology, University Hospital of Split, Croatia, for the year 2021. The age of the patients ranged from 26 to 89 years, of whom 27% were women. Sixty seven percent of all GBS patients recovered from COVID-19 infection, whereas post-vaccinal polyradiculoneuritis was detected in 6%. Forty four percent of the patients who developed GBS had a severe form of COVID-19 infection. Forty percent of patients were treated with intravenous immunoglobulins (IVIG), followed by therapeutic plasma exchange (PLEX) in 27%. After the therapy, improvement was observed in 13 patients, while two patients died. The results suggest that SARS-CoV-2 triggers GBS because it follows a similar pattern of infection as the other viral and bacterial agents that contribute to the onset of GBS. There is no evidence that prior infection with COVID-19 worsens the clinical presentation of GBS.